2014
DOI: 10.1007/978-3-319-08004-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Bacilli and their Enzymes in Composting

Abstract: Thermophilic Bacilli play a key role in the biocomposting process. Methods for analysing microbial diversity and community structure during composting have been especially helpful in characterising this process more completely. Thermophilic Bacilli account for the most prevalent group of thermophiles present in compost and the role of these bacteria in composting is highlighted. The spectrum of thermophilic Bacilli and the progression of their enzymes during the composting process are discussed, with a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…For example, diversity studies have revealed the apparent domination of the members of this class in geothermal sources with temperature optimums ranging from 45 to 70 °C, such as hot springs [ 7 , 8 , 9 , 10 , 11 , 12 ] and deep-sea hydrothermal vents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] to name a few. The thermophilic family Bacillaceae also account for the most prevalent group of thermophiles present during the thermophilic temperature phases in the compost, with represented genera of Geobacillus, Bacillus, Ureibacillus, Brevibacillus, Paenibacillus, and Aneureinibacillus , now highlighted in many studies [ 20 , 21 , 22 , 23 , 24 , 25 ]. In contrast, Larkin et al (1966) reported the distribution and diversity of ninety psychrophilic isolates of Bacillus from the soil, mud, and water by selective enrichment at 0 °C [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, diversity studies have revealed the apparent domination of the members of this class in geothermal sources with temperature optimums ranging from 45 to 70 °C, such as hot springs [ 7 , 8 , 9 , 10 , 11 , 12 ] and deep-sea hydrothermal vents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] to name a few. The thermophilic family Bacillaceae also account for the most prevalent group of thermophiles present during the thermophilic temperature phases in the compost, with represented genera of Geobacillus, Bacillus, Ureibacillus, Brevibacillus, Paenibacillus, and Aneureinibacillus , now highlighted in many studies [ 20 , 21 , 22 , 23 , 24 , 25 ]. In contrast, Larkin et al (1966) reported the distribution and diversity of ninety psychrophilic isolates of Bacillus from the soil, mud, and water by selective enrichment at 0 °C [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The largest variability for this trait was obtained for strains of the genera from the phylum Firmicutes, Brevibacillus , Geobacillus , Bacillus , Aeribacillus , and the Actinobacteria Microbacterium , which had representatives in both extremes of the temperatures tested. All these Firmicutes genera have been earlier reported to grow in a wide range of temperatures ( Bhattacharya and Pletschke, 2014 ; Verma et al, 2019 ), but Microbacterium usually grows at temperature lower than 44°C ( Fidalgo et al, 2016 ). Chelatococcus strains were optimal at 30°C and 40°C, whereas it was over 40°C for the strains of the genera Paenibacillus , Terribacillus , and Ureibacillus .…”
Section: Resultsmentioning
confidence: 99%
“…The unique representative of Lysinibacillus had optimal growth at 20°C ( Figure 2A ), that is, in the range of growth temperature of the genus (16°C–45°C) ( Ahmed et al, 2007 ). Xyl activity, thermotolerance, and thermophilia are common traits among Firmicutes, especially for bacilli and related genera ( Bhattacharya and Pletschke, 2014 ). In fact, Geobacillus , Paenibacillus , and Bacillus , our predominant isolates, are the most widely reported thermophilic bacteria for their ability to produce thermostable Xyl ( Verma et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Isolate 2B40 showed 99% similarity with Bacillus licheniformis KP081r, while isolate 20B40 presented 99% similarity with Bacillus paralicheniformis PB61. Species of Bacillus species have been isolated and reported to play a major role in agro-waste degradation during composting (Bhattacharya and Pletschke 2014;Kinet et al 2015). Amore et al (2013), also reported the isolation of novel cellulolytic bacteria most of which belong to the members of genera Bacillus.…”
Section: Identification Of Isolate 2b40 and 20b40 Using 16s Rdnamentioning
confidence: 99%